The export and import activities of Paxar Bangladesh Limited (a subsidiary of Avery Dennison Corporation) - Milon, Md. Ferdows Alam (BRAC Univeristy, 2017)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Master of Business Administration, 2017.